The Religious Association Scale as an "Abilities" Measure of the Religious Factor in Personality - Embree, Robert A. (Journal for the scientific study of religion, 1970)
A measure of religiosity was developed, based on subjects' associations to 80 consonant-vowel-consonant groups, which had previously been scaled for religious association value. Subjects were not given ambiguous instructions intended to measure how many religious associations might spontaneously emerge. Rather, subjects were specifically instructed to form religious associations, if they could, and to use the association in a complete sentence. The distinction is based on that made by Wallace between dispositional and capability conceptions of personality. Responses could be reliably scored on a three-point scale of religiosity. Sex differences in the expected direction provide a preliminary suggestion of validity.